2002
DOI: 10.1016/s0022-5347(05)64223-1
|View full text |Cite
|
Sign up to set email alerts
|

The Ascending Testis and the Testis Undescended Since Birth Share the Same Histopathology

Abstract: The ascending testis has the same germ cell count as the primary undescended testis. Yearly followup by the primary care physician is recommended for patients with retractile testes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
48
0
15

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(67 citation statements)
references
References 13 publications
4
48
0
15
Order By: Relevance
“…As mentioned above, biopsies taken from ascending testes showed comparable histological findings to biopsies taken from the contra lateral descended testes and primary undescended testes (Rusnack SL et al 2002). Gracia et al (Gracia J et al 1997) reported an impaired spermatogenic potential in 25/ 35 (71.4%) biopsied ascending testes.…”
Section: Acquired Udt and Fertilitymentioning
confidence: 53%
See 1 more Smart Citation
“…As mentioned above, biopsies taken from ascending testes showed comparable histological findings to biopsies taken from the contra lateral descended testes and primary undescended testes (Rusnack SL et al 2002). Gracia et al (Gracia J et al 1997) reported an impaired spermatogenic potential in 25/ 35 (71.4%) biopsied ascending testes.…”
Section: Acquired Udt and Fertilitymentioning
confidence: 53%
“…A third hypothesis proposed by Rusnack et al (Rusnack SL et al 2002) who found that primary undescended testes, ascending testes and the contralateral descended testes share the same histopathology concerning the total and differential germ cell counts per tubule. These findings suggest that an endocrine defect could be the cause of acquired UDT, since no thermal effect can be blamed for the decreased germ cell count in the descent testes.…”
Section: Pathogenesismentioning
confidence: 97%
“…Men with a history of ascended testis still have subfertility with abnormal spermatogenesis, as subsequent heat-induced defective germ cell maturation in childhood is likely to occur with ascent. On the other hand, Rusnack et al [47] found no difference in histology of ascended testis and primary undescended testis as both groups had equally depressed germ cell numbers. This could be explained by the relatively late age (7 years) of orchidopexy in their group.…”
Section: Risk Of Testicular Neoplasiamentioning
confidence: 95%
“…It has been shown that ascending testis shares a similar histopathology to congenital undescended testis. 31 Orchidopexy is also recommended.…”
Section: Clinical Evaluationmentioning
confidence: 99%